Berjabat Tangan dengan Lawan Jenis - Nurul Huda (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2015)
It has been a common practice among society that shaking hands is a symbol of social relations bounding among people, good business relationships, friendship, kinship and others. But, Islam as a religion that aims to regulate the moslem welfare , has been set severel rules in shaking hands between man and woman. Because Islam anticipates its negative impact such as relationship without the status of